Qualidade de vida no trabalho: um estudo em empresas que publicam balanço GRI - Roble, Gilmara Lima de Elua (2012)
Quality of life is an increasingly discussed topic in the media, in business and even in familiar surroundings. The corporate world is already aware of the importance of quality of life and the need to create better conditions for the welfare of the employees. The objective of this study is to analyze the quality of work life balance in the companies that publish GRI, to check quality of work life is within the "triple bottom line" of sustainability and analyze the satisfaction of their workforce as the main factors that interfere with their quality of life. Search the quality of work life is embedded in the dimensions of sustainability is important to solidify the congruence of the two themes. To support the research work is divided into three chapters that were the basis for the study. Chapter 1 presents the Quality of Work Life, bringing a historical review of the QWL movement, from its origins to the present day, introducing the concepts of the principal authors. Chapter 2 focuses on Sustainability in Organizations, their origin and evolution, its dimensions and indicators. For the research were chosen six companies that were among the 150 best companies to work for, in 2011, analyzing the indicators of QWL, and that in the same year, were listed companies with Sustainability models in between 21 Sustainability Guide companies to the indicators used the 150 best companies to work for, these 06 companies were evaluated satisfactorily covering the GRI indicators in the Balance